Analisis dan Perancangan Sistem Informasi Audit Internal Berbasis Web (Studi pada PT Wijaya Karya Beton Tbk) - Anavira Nuravita; Welly Purnomo; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Internal audits of PT Wijaya Karya Beton Tbk are still carried out conventionally, causing problems such as paper waste, inefficient time in completing a process, and delays in sending audit reports and RTP reports. Therefore, the research is carried out to analyze and design an Internal Audit Information System that is able to facilitate internal audit. The method used in this research is the Waterfall model. In the first stage, requirements analysis is carried out through interviews and documentation studies with the Bureau of Quality, Safety, Health, Environment & Management Systems (QSHE & SM), then in the next stage a design is carried out with an object-oriented approach. After the analysis and design is complete, the results of the analysis and design are evaluated. The results of this research include business processes modeling, requirements identification, use cases modeling, design of information systems, and evaluation with traceability matrix and System Usability Scale. This research concludes that all features of the system meet the user requirements, all functional requirements of the system come from features on the system, use cases have been defined in accordance with the features of the system, and use cases can be traced to activity diagrams and sequence diagrams. The design of the Internal Audit Information System interface is also considered to have good usability and is acceptable.